(untitled) (UNED Research Journal, 2018)
Heavy metals at the trace level have been the subject of study for several decades, however, this research focuses on copper, iron and zinc, which have been quantified in wine by the technique of atomic absorption, generally obtaining results within the permissible limits. We propose a method to analyze the indicated metals, in distilled alcoholic beverages as well as in the water used in the beverage manufacturing process. We tested acid digestion by comparing two methods, using HNO3-HCl and only HNO3, to reduce interferences due to organic matter in the alcohol samples; Based on the evidence and the acceptance criteria for accuracy and precision, the need for digestion with only HNO3 in the alcohol samples is justified. In the case of water samples, digestion is not necessary. In this way, we obtained as a result an atomic absorption methodology with the adequate performance parameters for the accurate and reliable quantification of metals in the study samples.